Development of measurement system of cutting load response in nipper blade, and estimation of wedge angle effect on cutting characteristics and shear edge trace of polystyrene bars - Thepwachara Ruchirabha; Shigeru Nagasawa (AIMS Materials Science, 2019)
This research was aiming to investigate cutting characteristics of Polystyrene square bars that were cut by three different type nippers. A pair of rotational-linked fixture of nipper arm was designed and developed for measuring the cutting load and displacement of the nipper. After discussing the calibration of nipper’s inside spring force and the stiffness of fixture, three types of nippers which had the representative apex angles of 72° (the big nipper), 42° (the medium nipper), and 13° (the small nipper), were examined with a 3 mm square bar of polystyrene under keeping the indentation velocity at V = 1 mm·s−1. It was clarified that the capability of designed fixture JIG was consistent for measuring and comparing the cutting response of several nippers. Using the fixture JIG and three kinds of nippers, the cutting peak maximum force, the cutting energy and the sheared profile (shear edge trace) of the PS bar specimen were investigated. When using the big and medium nippers, there were unstable cracks and dynamic large force drop (as a breaking down) during the cutting process after passing the necked stage, while the small nipper had the lowest peak line in the early stage (at the pushed stage) and any complicated cracks and large force drop were not detected, due to the wedge effect of blade apex angle and frictional restriction of counter anvil. Furthermore, the asymmetric effects of upper/lower wedge indentation were detected by using a microscope CCD camera during the cutting process.